2016
DOI: 10.1111/aogs.12918
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based registry study evaluating surgery in newly diagnosed uterine cancer

Abstract: Minimally invasive surgery in uterine cancer patients reduces days to normal activities of daily living, number of days to return to work, length of hospital stay, and blood loss in patients without and with lymph node dissection and in obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
1
14
1
Order By: Relevance
“…This is supported by one registry study that showed a significantly lower proportion of women staying three nights or more in hospital . One other registry study reports a non‐significant shorter stay in the robotic group . Return to normal activity is shorter for robotics in the one study that reports this outcome in the meta‐analysis .…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…This is supported by one registry study that showed a significantly lower proportion of women staying three nights or more in hospital . One other registry study reports a non‐significant shorter stay in the robotic group . Return to normal activity is shorter for robotics in the one study that reports this outcome in the meta‐analysis .…”
Section: Discussionmentioning
confidence: 82%
“…In addition, there was one randomised controlled study (Table ). Furthermore, seven papers reporting data from registries were carefully read and used for comparative discussion in the relevant section of this paper …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The introduction of minimal-invasive surgery, especially robotassisted surgery, has developed rapidly the last ten years in Sweden as well as in other countries and has lead to enhanced recovery for women with endometrial cancer. 35 The new techniques have decreased the surgical risks even for elderly women, 36,37 which probably will increase the patient population suitable for lymphadenectomy. In the future, the introduction of sentinel node mapping might even further minimize surgical trauma for this patient group.…”
Section: Cancer Epidemiologymentioning
confidence: 99%